Identification of a cytisine-based EED-EZH2 protein-protein interaction inhibitor preventing metastasis in triple-negative breast cancer cells - Shasha Cheng; Guan-Jun Yang; Wanhe Wang; Ying-Qi Song; Chung-Nga Ko; Quanbin Han; Dik-Lung Ma; Chung-Hang Leung (Acta Materia Medica, 2022)
Enhancer of zeste homolog 2 (EZH2) is activated in breast cancer, particularly in triple-negative breast cancer (TNBC), and is critical for cell invasion. It interacts with embryonic ectoderm development (EED) in maintaining cancer stem cells (CSC) and epithelial-mesenchymal transition (EMT) properties, hence promoting CSC metastasis. Because the association of EZH2 with EED promotes the catalytic activity of EZH2, inhibiting the EED-EZH2 interaction is a potential therapeutic strategy for treating EZH2-dependent cancer. Although several EED-EZH2 protein-protein interaction (PPI) inhibitors have been developed, few target EED. Here, we identified that a cytisine derivative compound (1) potently binds EED, thus blocking the EED-EZH2 PPI. Compound 1 was found to inhibit cell proliferation and suppress the growth of 3D tumor spheres of TNBC cells. Moreover, by reversing EMT and decreasing the ratio of CSCs, the compound inhibited TNBC metastasis and invasion ability. Therefore, targeting EED to disrupt the EED-EZH2 PPI may provide a new approach for treating TNBC metastasis. To our knowledge, compound 1 is the first cytisine-based EED-EZH2 PPI inhibitor preventing metastasis in TNBC cells. This study may provide a new avenue for the development of more efficacious EED-EZH2 PPI inhibitors in TNBC treatment.